Single-nucleotide polymorphisms in Orai1 associated with atopic dermatitis inhibit protein turnover, decrease calcium entry and disrupt calcium-dependent gene expression. (10th October 2019) - Yeh, Yi-Chun; Lin, Yu-Ping; Kramer, Holger; Parekh, Anant B
Abstract: Loss-of function mutations in Orai1 Ca 2+ channels lead to a form of severe combined immunodeficiency, auto-immunity, muscle hypotonia and defects in dental enamel production and sweat gland function. Two single-nucleotide polymorphisms (SNPs) in Orai1 have been found and localize to the second extracellular loop. These polymorphisms associate with atopic dermatitis but how they affect Ca 2+ signalling and cell function is unknown. Here, we find that Orai1–SNPs turnover considerably more slowly than wild type Orai1 and are more abundantly expressed in the plasma membrane. We show a central role for flotillin in the endocytotic recycling of Orai1 channels and that endocytosed wild type Orai1 is trafficked to Rab 7-positive late endosomes for lysosomal degradation. Orai1–SNPs escape the degradation pathway and instead enter Rab 11-positive recycling endosomes, where they are returned to the surface membrane through Arf6-dependent exocytosis. We find that Orai1–SNPs escape late endosomes through endosomal pH regulation of interaction between the channel and flotillin. We identify a pH-sensitive electrostatic interaction between positively charged arginine in extracellular loop 2 (K210) and a negatively charged aspartate (D112) in extracellular loop 1 that helps determine Orai1 turnover. The increase in membrane Orai1–SNP leads to a mis-match in Orai1–STIM stoichiometry, resulting in inhibition of Ca 2+ entry and Ca 2+ -dependent gene expression. Our results identify new strategies for targeting atopic dermatitis.